Effect of Bokashi Fertilizer and Monosodium Glutamate on Growth and Yield of Cayenne Pepper (Capsicum frutescens l.) - Zahanis Zahanis; Fatimah Fatimah; Utria Nurval Utami (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2021)
This study aims to determine The purpose of this experiment was to determine the interaction of bokashi fertilizer and monosodium glutamate on the growth and yield of cayenne pepper (Capsium frutescens L.). This experiment used a completely randomized design (CRD) factorial. The first factor is the dose of rice straw bokashi which consists of 4 levels, namely: 0 g/polybag, 50 g/polybag, 100 g/polybag, 150 g/polybag. The second factor is the dose of MSG which consists of 3 levels, namely: 0 ml/l water, 4 ml/l water, 8 ml/l water. Based on the results of the study, it was found that the application of bokashi fertilizer and monosodium glutamate interacted with the growth and yield of cayenne pepper (Capsicum frutescens L.), namely producing the weight of the fruit plants by giving 150 g/polybag of bokashi fertilizer and 8 ml/l of MSG water, namely 60.67 g of weight fruit.